Pitta Shamaka drugs as anti-inflammatory agents in Paripluta Yoni Vyapada - Mishra, Jitendrakumar Vinaykumar (International journal of health sciences, 2021)
Background: Paripluta Yoni Vyapada is one of the twenty Yoni Vyapadaas (gynaecological disorders) described in Ayurvedic classics, characterised by excessive vaginal discharge associated with burning sensation, itching, and inflammation — a clinical picture strongly dominated by vitiated Pitta dosha. Contemporary gynaecology identifies this presentation as correlating with conditions such as infective vulvovaginitis, cervicitis, pelvic inflammatory disease (PID), and non-infective inflammatory vaginopathies. Standard modern management relies on antimicrobial and anti-inflammatory pharmacotherapy, while Ayurveda prescribes Pitta Shamaka (Pitta-pacifying) dravyas which inherently possess Shothahara (anti-inflammatory), Jvaraghna (antipyretic), Vishagna (antimicrobial), and Vedanasthapana (analgesic) properties. Objective: To conduct a systematic review of the classical Ayurvedic description of Paripluta Yoni Vyapada, identify the Pitta Shamaka drugs prescribed in classical texts for its management, analyze their anti-inflammatory phytochemical and pharmacological profiles, and correlate these findings with contemporary understanding of vaginal and pelvic inflammatory pathophysiology. Methods: Classical texts including Charaka Samhita, Sushruta Samhita, Ashtanga Hridayam, Harita Samhita, Kashyapa Samhita, Bhavaprakasha, and relevant Nighantu texts were reviewed. A parallel search of PubMed, Scopus, Web of Science, and AYUSH Research Portal (1980-2025) was conducted for pharmacological studies on the identified Pitta Shamaka drugs with specific focus on anti-inflammatory, antimicrobial, and gynaecological applications.